Does Social Media Drive Business Performance? Investigation of Top Management Team in Inspection Services Companies - Putra, Fadhila Rianda; Balqiah, Tengku Ezni (Jurnal Minds: Manajemen Ide dan Inspirasi, 2025)
Social media has become a transformative force in both B2C and B2B marketing. This study contributes novel insights by integrating top management participation, absorptive capacity, and customer relationship management capabilities (CRMC) into a single framework to explain how social media marketing (SMM) assimilation shapes firm performance in resource-constrained B2B service contexts. Focusing on inspection service companies in Indonesia, we examine the influence of Top Management Team participation on SMM assimilation, with absorptive capacity as a moderator and CRMC as a mediator. Using a quantitative design and Partial Least Squares Structural Equation Modeling (PLS-SEM) on 222 respondents across 74 business units, findings show that SMM assimilation affects performance differently across marketing functions, strengthening sales through pricing and channels while primarily enhancing relationships via product and promotion. Results confirm that absorptive capacity enhances managerial impact and CRMC mediates performance outcomes. The implications guide managers in strengthening digital competitiveness within inspection service firms.